Optical conductivity of the Hubbard chain away from half filling - Tiegel, A; Veness, T; Dargel, P; Honecker, A; Pruschke, T; McCulloch, I; Essler, F (American Physical Society, 2016)
We consider the optical conductivity σ1(ω) in the metallic phase of the one-dimensional Hubbard model. Our results focus on the vicinity of half filling and the frequency regime around the optical gap in the Mott insulating phase. By means of a density-matrix renormalization group implementation of the correction-vector approach, σ1(ω) is computed for a range of interaction strengths and dopings. We identify an energy scale Eopt above which the optical conductivity shows a rapid increase. We then use a mobile impurity model in combination with exact results to determine the behavior of σ1(ω) for frequencies just above Eopt which is in agreement with our numerical data. As a main result, we find that this onset behavior is not described by a power law.